Jihad in Paradise: Islam and Politics in Southeast Asia by Mike Millard (New York: M.E. Sharpe, Inc., 2004. 155 pages.) (American Journal of Islam and Society, 2006)
Jihad in Paradise explores cultural and religious interaction in Singapore andcompares this with the intolerant radical Islamism threatening the countryand Southeast Asia in general. Millard, a senior journalist who first workedon East Asia and then Southeast Asia, artfully conveys his descriptive yetanalytical narrative of how Southeast Asia underwent radical change due, in large part, to the influence of global and regional terrorism. Meanwhile,Singapore has yet to move forward by allowing greater political freedom anddeveloping mutual dialogue and cooperation between its different religiouscommunities. The Malay minority must also adjust itself to such pragmaticeconomic and political climates. Singapore’s future depends on how well itmanages multicultural diversity and balances its economic progress andpolitical democracy.The book is divided into six chapters. In his introduction, Millardobserves how Singapore and Southeast Asia were generally prosperous andpeaceful until the Asian financial crisis of 1997-98, 9/11, and the 2002 Balibombings. He realizes that his book is not an “inside story,” for he regardshimself as only journalist who is deeply interested in human realities andtheir regional and global dimensions ...